Healthy aging-relevant goals: the role of person-context co-construction - Wahl, Hans-Werner; Hoppmann, Christiane A.; Ram, Nilam; Gerstorf, Denis (The journals of gerontology. Series B, Psychological sciences, social sciences, 2021)
This article considers how individuals’ motivation for healthy aging manifests within the myriad of different contexts that older adults are embedded in as they move through later life.Drawing on the concept of co-construction, we argue that persons and contexts both contribute to the emergence, maintenance, and disengagement from healthy aging relevant goals in adulthood and old age.To promote the understanding of such co-constructive dynamics, we propose four conceptual refinements of previous healthy aging models. First, we outline various different, often multidirectional, ways in which persons and contexts conjointly contribute to how people set, pursue, and disengage from health goals. Second, we promote consideration of context as involving unique, shared, and interactive effects of socio-economic, social, physical, care/service, and technology dimensions. Third, we highlight how the relevance, utility, and nature of these context dimensions and their role in co-constructing health goals change as individuals move through the Third Age, the Fourth Age, and a terminal stages of life. Finally, we suggest that these conceptual refinements be linked to established (motivational) theories of lifespan development and aging.In closing, we outline a set of research questions that promise to advance our understanding of the mechanisms by which contexts and aging persons co-construct healthy aging relevant goals and elaborate on the applied significance of this approach for common public health practices.
Gesehen am 01.02.2022